The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1158/0008-5472.can-07-5949
|View full text |Cite
|
Sign up to set email alerts
|

Targeting N-Cadherin Enhances Antitumor Activity of Cytotoxic Therapies in Melanoma Treatment

Abstract: Malignant transformation in melanoma is characterized by a phenotype ''switch'' from E-to N-cadherin, which is associated with increased motility and invasiveness of the tumor and altered signaling, leading to decreased apoptosis. We hypothesized that the novel pentapeptide (ADH-1), which disrupts N-cadherin adhesion, could sensitize melanoma tumors to the cytotoxic effects of chemotherapy. N-cadherinexpressing human melanoma-derived cell lines were used to generate xenografts in animal models to study isolate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
94
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 44 publications
0
94
0
Order By: Relevance
“…However, more recent data suggest that downregulation of Mcl-1 alone is not sufficient to induce cell death or enhance the sensitivity of cells to chemotherapy or radiation (19,42), consistent with our observations. Systemic treatment of rats with a small peptide inhibitor of N-cadherin has recently been shown to increase the levels of melphalan adducts in tumor cells in our xenograft melphalan ILI animal model (43). Likewise, alterations in drug delivery have been reported for other vascular targeting agents, including Gleevec (imatinib) and Avastin (bevacizumab; refs.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, more recent data suggest that downregulation of Mcl-1 alone is not sufficient to induce cell death or enhance the sensitivity of cells to chemotherapy or radiation (19,42), consistent with our observations. Systemic treatment of rats with a small peptide inhibitor of N-cadherin has recently been shown to increase the levels of melphalan adducts in tumor cells in our xenograft melphalan ILI animal model (43). Likewise, alterations in drug delivery have been reported for other vascular targeting agents, including Gleevec (imatinib) and Avastin (bevacizumab; refs.…”
Section: Discussionmentioning
confidence: 67%
“…Our results show that this approach may be effective not only with regionally administered chemotherapeutic agents like temozolomide (currently being evaluated in a phase I dose escalation ILI trial) but also with other systemically administered targeted agents or modulators. In addition to sorafenib, as described here, preclinical studies using systemically administered agents that target the glutathione detoxification system, such as the reduced glutathione-depleting agent buthionine sulfoximine, and cell adhesion, such as the small peptide inhibitor of N-cadherin ADH-1 (43,49), have proved very effective in improving tumor responses. Phase I/II clinical trials examining the efficacy of these agents, including sorafenib, to enhance the response of melanoma to ILI with melphalan are currently in progress or under development.…”
Section: Discussionmentioning
confidence: 99%
“…Many novel drugs are being developed that target specific molecular or genetic lesions, and although targeted therapies alone often show only modest antitumor activity (48), it is likely that when combined with standard chemotherapies, the responses will be higher and more durable (28). Our laboratory has recently shown that targeted disruption of N-cadherin signaling with the small molecule ADH-1 can significantly improve the antimelanoma activity of temozolomide in a murine xenograft model (49). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…N-cadherin overexpression via cadherin switching was observed in various invasive cancer cell lines and tumors and, therefore, is emerging as a potential therapeutic target. ADH-1, a peptide antagonist that disrupts N-cadherin-mediated adhesion, has been shown to inhibit cell growth and motility in vitro, as well as tumor growth and invasion in vivo (11,12); ADH1 is currently undergoing phase 1 clinical trials.…”
mentioning
confidence: 99%